Evaluation of Serum 25-Hydroxyvitamin D as a Predictor of Carotid Intima-Media Thickness and Carotid Total Plaque Area in Nonsmokers: The Tromsø Study. (20th November 2013) - Kamycheva, Elena; Johnsen, Stein Harald; Wilsgaard, Tom; Jorde, Rolf; Mathiesen, Ellisiv B.
Abstract : Objective . Altered calcium homeostasis has been linked to increased intima-media thickness (IMT) and plaques. We aimed to investigate whether serum 25-hydroxyvitamin D (25(OH)D) and serum calcium are associated with IMT and plaques in nonsmoking population. Methods . Ultrasound of the right carotid artery with the measurements of IMT and plaques was performed in 4194 nonsmoking subjects with available measurements of serum 25(OH)D and total calcium. Linear regression was applied to study the linear relationships between variables. Multinomial logistic regression was used to evaluate predictors of increased IMT and total plaque area (TPA), adjusted for age, body mass index, systolic blood pressure, and total cholesterol. Results . There was no significant linear relationship between mean IMT, TPA, and either serum 25(OH)D or total serum calcium. One SD increase in serum 25(OH)D was independently associated with increased odds of being in the highest quartile of IMT in men (OR 1.30, 95% CI 1.12, 1.51). In women, 1 SD increase in serum 25(OH)D was independently associated with increased risk of being in the upper tertile of TPA (OR 1.15, 95% CI 1.01, 1.33). Conclusions . Impaired calcium homeostasis has no consistent association with mean IMT and TPA; however, increased serum 25(OH)D may predict subclinical atherosclerosis in nonsmokers.